Effect of V2O5 interlayers in V2O5/Ge8Sb92 superlattice-like film on thermal stability and size scaling. (October 2020) - Xu, Yongkang; Hu, Yifeng; Sun, Song; Zhu, Xiaoqin; Lai, Tianshu; Song, Sannian; Song, Zhitang
Highlights: Compared with GeSb, the Tc  increased from 197 °C of GeSb to 233 °C of V2 O5 /Ge8 Sb92 . The data retention temperature for ten years of V2 O5 (4 nm)/Ge8 Sb92 (6 nm) is 171.2 °C. The larger band gap  Eg  makes V2 O5 /Ge8 Sb92  have higher Ra  and lower power consumption. After phase transformation, the volume change of V2 O5 /Ge8 Sb92  is smaller than GST. Abstract: In this paper, the superlattice-like V2 O5 /Ge8 Sb92 films are studied. Compared with Ge8 Sb92 film, V2 O5 /Ge8 Sb92 films have a high crystallization temperature (~233 °C), a large amorphous resistance (~3.4 × 10 7  Ω) and good data retention temperature (~171.2 °C) for ten years. The volume change rate of V2 O5 /Ge8 Sb92 superlattice-like film is only 1.855% during the crystallization, which can guarantee a better contact with the electrode when it is applied in the phase-change memory. By adding of V2 O5 interlayers, the thermal stability and reliability of Ge8 Sb92 film have been greatly improved.